A bibliometric review of laboratory safety in universities. (December 2019) - Yang, Yunfeng; Reniers, Genserik; Chen, Guohua; Goerlandt, Floris
Highlights: The study applied bibliometric in reviewing university laboratory safety research. Most influential countries, journals, scholars, and papers were identified. Cooperation among main research countries, institutions and authors were analyzed. The research topics and trends were identified using terms co-occurrence network. Several avenues for future research are proposed on university laboratory safety. Abstract: Although there is a growing field of research focusing on university laboratory safety, accidents in such contexts still occur relatively frequently. Therefore, it is significant to summarize current research status and gaps, and to propose future research directions in the field of university laboratory safety. In this paper, a bibliometric analysis method was applied to gain an overall view of the developments, focus areas, and trends in this field of safety research. A total of 219 scientific publications on university laboratory safety were identified and screened from the database of Web of Science, covering 44 countries or regions, 254 research institutions, 575 authors, 126 publication sources, and 70 subject categories. Bibliometric data such as annual growth trend and distribution of subject categories were analyzed by using descriptive statistics. The most productive and influential countries, institutions, authors, and their cooperation networks were identified from co-citation maps created by VOSviewer. Further analysis was carried out to find out the core publications and publication sources in this field. Insights in the focus areas and research topics over time were obtained through terms co-occurrence analysis. The results indicate that university laboratory safety is a highly multidisciplinary research field. However, it is still a young discipline and belongs to the minority research field when compared with other safety domains. Several avenues for future research are identified to advance and make progress in this field.